2021
DOI: 10.1073/pnas.2024463118
|View full text |Cite
|
Sign up to set email alerts
|

Cardenolides, toxicity, and the costs of sequestration in the coevolutionary interaction between monarchs and milkweeds

Abstract: For highly specialized insect herbivores, plant chemical defenses are often co-opted as cues for oviposition and sequestration. In such interactions, can plants evolve novel defenses, pushing herbivores to trade off benefits of specialization with costs of coping with toxins? We tested how variation in milkweed toxins (cardenolides) impacted monarch butterfly (Danaus plexippus) growth, sequestration, and oviposition when consuming tropical milkweed (Asclepias curassavica), one of two critical host plants world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 51 publications
8
92
2
Order By: Relevance
“…Disentangling the relative contribution of nutrition, defenses, flight muscle would require additional studies focusing on just this species. Work by Agrawal et al 32 recently examined such mechanisms for larval performance on tropical milkweed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Disentangling the relative contribution of nutrition, defenses, flight muscle would require additional studies focusing on just this species. Work by Agrawal et al 32 recently examined such mechanisms for larval performance on tropical milkweed.…”
Section: Discussionmentioning
confidence: 99%
“…Although relationships between milkweeds, monarchs, and toxins have played a central role in our understanding of coevolution, plant defense, sequestration, and animal behavior 17 , understanding the mechanistic link between host plant chemicals, sequestration and adult flight is challenging. There is some recent evidence that cardenolides can be a burden for monarchs and that there are costs to sequestration 32 . In vitro work by Petschenka et al 75 demonstrated that certain cardenolides can be strong inhibitors of neural function in monarchs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most beneficial substitutions occur in the amino acid residues 111, 119 and 122, and additionally in 786 and 797 in specific clades, conferring enhanced tolerance to cardenolides (Dobler et al, 2012; Karageorgi et al, 2019). In response, defence evolution in plants has resulted in the production of specific cardenolide compounds with particularly high potency against resistant sodium pumps (Agrawal et al, 2021; Petschenka et al, 2018). Nonetheless, since not all milkweed insects show the same sodium pump insensitivity (i.e., different number of genetic substitutions), whether the degree of cardenolide tolerance in insects targeting different plant tissues matches tissue‐specific defence chemistry remains untested.…”
Section: Introductionmentioning
confidence: 99%